The Role of Ursodeoxycholic Acid and Phenobarbital in a Child with Cholestasis: A Longitudinal Study - Ringoringo, Harapan Parlindungan (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Cholestasis is a condition that starts in the 1st months of life and progresses with direct (conjugated) bilirubin increase and jaundice as a result of impaired bile production or excretion. Its incidence is known as 1 in 2500 live births. This study shows the effectiveness of ursodeoxycholic acid (UDCA) and phenobarbital in infant cholestasis treatment. CASE REPORT: A 28-days-old boy came with a complaint of yellow eyes. At the age of 3 days, the patient looked yellow, had a fever and difficulty drinking, received phototherapy. After 2 weeks of treatment with neonatal sepsis, the patient was discharged in a stable. The skin appears yellow. The laboratory results show anemia, elevated conjugated bilirubin, and signs of infection; the abdominal ultrasonography shows that the liver and gallbladder were normal. The diagnosis is cholestasis due to sepsis. After 3 months of treatment with UDCA and phenobarbital, jaundiced disappeared, and liver function tests were normal. When the patient is 2 ½ years old, the growth and development suit his age. CONCLUSION: Early diagnosis and timely treatment of UDCA and phenobarbital play a role in cholestasis improvement. On long-term observation, the child’s growth and development are suitable according to his age and average laboratory results.